Barriers to Innovation: Experience of Ecuadorian Small and Medium Entreprises (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
The innovation barriers to small and medium-sized enterprises affect their innovative process and influence their company development. In this empirical work, we analyze the cost, market, and knowledge barriers that impede or delay the development of innovative activities and projects in Ecuadorian SMEs. A logit estimation model uses fixed-effects panel data on a sample of 5,205 SMEs during the period from 2009–2014. The results show that small and young companies are more vulnerable to the perceived barriers of cost and knowledge. This is mainly due to high innovation costs and a lack of skilled staff that restricts organizational growth and market competitiveness.
Keywords: innovation barriers, SMEs, competitiveness, logit, panel data